The Role Of Peroxisome Proliferator-Activated Receptor (PPAR) Isoforms In The Pathogenesis Of Type 1 Diabetes In Male Non-Obese Diabetic (Nod) Mice [RA645.D5 G614 2008 f rb]. - Goh, Kenny Soen Keong (2008)
PPAR merupakan faktor transkripsi yang boleh meredakan tindakbalas imun apabila diaktifkan oleh ligan.